[PP.05.10] COMPARISON OF PULSE WAVE ANALYSIS PARAMETERS IN HYPERTENSIVE DIABETIC AND NON-DIABETIC PATIENTS IN A BRAZILIAN AMBULATORY CARE. (September 2016) - Resende, L.; Da Silva, M.A.V.; Resende, E.A.M.R.; Resende, J.A.M.; Da Silva, A.P.M.; Casemiro, A.L.M.; Jr, R.M. Lucas
Abstract : Objective: To evaluate and compare pulse wave analysis parameters in diabetic and non-diabetic hypertensive patients. Design and method: 98 hypertensive or hypertension suspected patients seen in the academic hypertension ambulatory from the Federal University of Triangulo Mineiro (UFTM), Brazil, between January and December 2015 had their pulse wave analysed by oscillometry - Mobil-O-Graph® PWA - EMI GmbH (Stolberg, Germany). Four consecutive measurements were taken every two minutes according to general recommendations for clinical studies of 'Clinical Applications of Arterial Stiffness, Task Force III: Recommendations for User Procedures (AJH 2002; 15: 445–452). All patients answered questions about personal and clinical data (medication use, cardiovascular risk factors, personal and family history of cardiovascular disease). The comparison between groups was performed using chi-square test and T Student test. Results: Data from 98 patients was analyzed. The results are shown in Table 1. Of the 98 patients 33 were diabetic and 65 non-diabetic. The average age was 58, 4 years and the average Body Mass Index (BMI) was 31, 3 kg/m2. 84 patients (85, 7%) were on anti-hypertensive medication. The mean systolic and diastolic central blood pressure was significantly higher in the group of diabetic patients in comparison with the group of non-diabetics (p = 0.0009 and 0.004 respectively). The mean peripheral sistolic blood pressure and pulse pressure were also significantly higher in the diabetic group (p = 0.0004 and 0, 004 respectively). The average pulse wave velocity (PWV) in the diabetic group was 9, 5 (SD: 1.7) whereas in the group of non-diabetic patients was 8, 6 (SD: 2.2) with a p value of 0.04. There was no statistical difference between the average augmentation pressure or augmentation index. Conclusions: The group of hypertensive diabetic patients had significantly higher central blood pressure, peripheral sistolic blood pressure and peripheral pulse pressure in relation to the group of non-diabetic hypertensive patients. The PWV also showed higher values in the group of diabetic patients, but the difference was not significant. Figure. No caption available.